Bound by her shocking secret - Green, Abby (Harlequin presents, 2021)
It takes all of Mia Forde's courage to tell jewelry tycoon Daniel Devilliers about their daughter. Desire drew them together, tragedy tore them apart, but he deserves to know he's a father. She wants nothing from Daniel--especially not his loveless proposal! --